Process mapping evaluation of medication reconciliation in academic teaching hospitals: a critical step in quality improvement. Issue 12 (30th December 2016) - Holbrook, Anne; Bowen, James M; Patel, Harsit; O'Brien, Chris; You, John J; Tahavori, Roshan; Doleweerd, Jeff; Berezny, Tim; Perri, Dan; Nieuwstraten, Carmine; Troyan, Sue; Patel, Ameen
Abstract : Background: Medication reconciliation (MedRec) has been a mandated or recommended activity in Canada, the USA and the UK for nearly 10 years. Accreditation bodies in North America will soon require MedRec for every admission, transfer and discharge of every patient. Studies of MedRec have revealed unintentional discrepancies in prescriptions but no clear evidence that clinically important outcomes are improved, leading to widely variable practices. Our objective was to apply process mapping methodology to MedRec to clarify current processes and resource usage, identify potential efficiencies and gaps in care, and make recommendations for improvement in the light of current literature evidence of effectiveness. Methods: Process engineers observed and recorded all MedRec activities at 3 academic teaching hospitals, from initial emergency department triage to patient discharge, for general internal medicine patients. Process maps were validated with frontline staff, then with the study team, managers and patient safety leads to summarise current problems and discuss solutions. Results: Across all of the 3 hospitals, 5 general problem themes were identified: lack of use of all available medication sources, duplication of effort creating inefficiency, lack of timeliness of completion of the Best Possible Medication History, lack of standardisation of the MedRec process, and suboptimal communication of MedRec issues between physicians, pharmacists and nurses. Discussion: MedRec as practised in this environment requires improvements in quality, timeliness, consistency and dissemination. Further research exploring efficient use of resources, in terms of personnel and costs, is required.